Medical mobile clinic bus - Ariffin, Farnaza (Faculty of Medicine, 2022)
On 27th September 2022, the Faculty of Medicine UiTM was officially handed a medical mobile clinic bus in a prestigious ceremony attended by delegates from the Noah Foundation, Faculty of Medicine and Faculty of Dentistry UiTM, local leaders, and Kluang district health authorities, Ministry of Health. The ceremony was officiated by the ‘Yang Amat Berhormat, Menteri Besar Johor’, Dato’ Onn Hafiz. The delegates from the Faculty of Medicine included the Dean, Associate Prof Dr. Fazah Akhtar Hanapiah, following with our ex-Dean, Hospital Al-Sultan Abdullah Deputy Director, Deputy Dean ICAN, the members of mobile clinic services committee, the heads of the department for Primary Care Medicine and Public Health, the faculty administrative and the corporate communication coordinator,